Macrophage activation syndrome in a patient with pulmonary inflammatory myofibroblastic tumour - Kuppe, Christoph (BioMed Central, 2012)
We describe for the first time a case of macrophage activation syndrome (MAS) in a patient with a history of inflammatory myofibroblastic tumour (inflammatory pseudotumour, IPT) of the lung and thoracic spine. The patient was admitted to the intensive care unit with a history of prolonged remitting fever, hepatosplenomegaly, bilaterally enlarged thoracic lymph nodes and an acute severe inflammatory response syndrome (SIRS). Up-regulated cytokine production (e.g. IL-1ß and IL-6), increased levels of ferritin and circulating soluble interleukin-2 receptor (sIL-2R, sCD25) led to the differential diagnosis of MAS. Bone marrow aspiration, the main tool for a definite diagnosis, revealed macrophages phagocytosing haematopoietic cells. Immunosuppressive therapy with corticosteroids and cyclosporine was an effective treatment in this patient.